2004
DOI: 10.1161/01.hyp.0000138405.94275.a2
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Hormonal Effects of Water Deprivation in Late-Term Pregnant Rats

Abstract: Abstract-Water-retaining hormones are stimulated during pregnancy allowing normal volume expansion. Because pregnant rats actively retain water, we postulate that water deprivation (WD) would cause a greater reduction in plasma volume in pregnant than in nonpregnant rats. To test this hypothesis, Sprague-Dawley pregnant and nonpregnant rats were water-deprived for 48 hours. At day 19 of pregnancy, or in the corresponding day in nonpregnant rats, they were randomly assigned to either a WD or a control (C) pair-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…In the present study, we confirmed earlier work showing that plasma volume expansion increase in a cumulative manner during pregnancy (2,7,26,27). Unexpectedly, we found that ENaC inhibition resulted in an increase in plasma volume in virgin rats, which we attribute to a rebound effect since this is the opposite of what would be expected with ENaC inhibition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we confirmed earlier work showing that plasma volume expansion increase in a cumulative manner during pregnancy (2,7,26,27). Unexpectedly, we found that ENaC inhibition resulted in an increase in plasma volume in virgin rats, which we attribute to a rebound effect since this is the opposite of what would be expected with ENaC inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…collecting duct; plasma volume expansion; sodium retention IN HUMANS AND RATS, PREGNANCY is accompanied by marked changes in cardiovascular function, renal function, and fluid homeostasis. These adaptations permit an increase in blood volume that will supply the growing uterus and fetus without the development of maternal hypertension.A normal healthy pregnancy is associated with a cumulative plasma volume expansion (PVE) (30 -50%) and avid sodium retention (2,26,27). Failure of this adaptation is associated with maternal morbidity/mortality and intrauterine growth restriction (3, 27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The expansion of plasma volume begins from the first trimester of gestation, increasing up to 1,250 ml in the third trimester [20] . Several studies have determined the importance of maternal adaptation to hemodynamic changes [21] and the relationship between inadequate adaptation in the early stages of pregnancy and reduced fetal growth [22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate volume expansion is associated with pregnancies compromised by fetal growth restriction (3,31). Furthermore, prevention of PVE through restriction of either sodium or water intake during late pregnancy in the rat results in growthrestricted pups (28,30).…”
mentioning
confidence: 99%